Glenoid Bone Loss in Posterior Shoulder Instability: Prevalence and Implications in Arthroscopic Treatment. Issue 7 (29th July 2014) - Hines, Adam Christopher; Cook, Jay B.; Shaha, James S.; Krul, Kevin P.; Tokish, John M.
Objectives: Glenoid bone loss is a well accepted risk factor for failure after arthroscopic stabilization of anterior glenohumeral instability. While less common than its anterior counterpart, posterior glenohumeral instability can be a significant source of disability in a young athletic population. It has been reported in as high as 10% of all glenohumeral instability cases. Bone loss in posterior instability, however, has been rarely discussed, and it is unknown whether this is commonly present, or clinically significant, in the treatment of posterior glenohumeral instability. Methods: A retrospective review was conducted at an active Military Treatment Facility (MTF) over a five-year period, between 1 Apr 2006 and 31 May 2011. Isolated, primary posterior instability cases which underwent arthroscopic posterior labral repair were identified. Preoperative imaging was available in all patients, and posterior glenoid bone loss was calculated using a standardized "perfect circle" technique often employed in the measurement of bone loss in anterior instability. All medical records were then reviewed to identify complications and reoperation rates from the primary repair. Patients were divided into two groups based on percentage bone loss. Outcomes were analyzed across all patients and within these groups. Results: There were 47 consecutive cases of primary, isolated posterior instability cases, with 44 males and 3 females. The average age at the time of surgery was 28.6 (range 20-47), 19 were documented to have returned to full duty. Posterior glenoid bone loss in excess of 10% was found in 15/47 (32%) of patients, while an additional 26% had no bone loss noted. Greater than 20% bone loss was noted in 2/47 (4.3%). The average across the cohort was 7.6% (range 0-21.5%). Bone loss was associated with younger age. Those with >10% loss had an average age of 25.6 years compared to 30.1 years in those with <10% bone loss (p=0.03). Those with >10% were not associated with lower return to duty, higher complications (i.e. persistent symptoms), or increased return to the operating room. Those who returned to full active duty did not have a significantly decreased bone loss versus those who did not (6.5 vs 8.3%, p=0.17). Conclusion: Posterior instability accounts for up to 10% of all glenohumeral instability. It carries a more an insidious onset, and acute dislocations are not as commonly reported. While anterior glenoid bone loss is known to significantly affect patient outcomes for anterior glenohumeral instability, our data suggests posterior glenoid bone loss may not have as direct of a clinical correlation to patient outcomes.